Nigun Poems - Marmer, Jake (Current Musicology, 2013)
This set of poems grew out of my experiences of listening and finding myself inside nigunim (pl; singular nigun or nign), Chassidic chants—mystical, usually wordless songs used as accompaniment for rituals—weddings, prayers, candle–lightings—collective beckoning of transcendence. The nigun experience is fraught with what Amiri Baraka called, referring to blues, the “re/feeling”—proximity and shape of personal history of encounters with unfathomable. Because most of the nigunim did not have lyrics they were comprised of scat—but a somber sort of a scat: “oi–oi”, “di–dai”, “bah–bom”, etc. Musical instruments were not used to accompany them, either, since most of the singing happened on the Sabbath, when instruments were put away. Rid of accompaniment, rid of lyrics, these stripped down chants were visceral and prayer–like but washed out of content, and filled, instead, with implication—with attempts. At the climax of one of his talks, balancing at the edge of the cognitive void, Rabbi Nachman of Breslov reportedly said: “And even to this, too, there’s an answer. But that answer is necessarily a song.” These poems attempt to reimagine the sensation of locating oneself inside a nigun.